Os impactos éticos da edição genética: o conflito ético da modificação genética da espécie humana - Brito, Lucas Lacerda Aragão de (2020)
The present paper aims to analyze the ethical and legal impacts caused by advances in genetic modification technologies and the emergence of new tools such as CRISPR / CAS9 and their consequent impacts on the sciences and the world community. It claims that the national Biosafety Law does not cover the new technologies of genetic modification, since it avoids the ethical and moral debate that these technologies raise. Making use of Hans Jonas‟ concept of responsibility, the study proposes a practical ethics designed for the technological future and its innovations‟ consequences over the global community and the future generations. Regarding the debate about the impacts of these technologies on the individual and it‟s selfconsciousness, it is chosen as a possible answer the concept of liberal Eugenics present on Habermas‟ theory. As a conclusion, the study brings both theories, as well as the principles of bioethics, as an answer for ethical thinking that aims at protecting the well-being of humanity and how the individual understands itself, affirming that these theories should also guide the legal regulations on new genetic manipulation technologies. Regarding the methodology, this exploratory-level research relies on a qualitative and essentially bibliographic nature, choosing the hypothetical deductive approach, specifically. The procedure methods chosen were the monographic, as well as the historical.